A comparative study of Cooperative learning versus traditional approach in elementary mandarin class/ Tan Teow Ghee…[et al.] - Tan, Teow Ghee; Ooi, Ai Kee; Dourado, Rita Maria (Research Management Institude, 2005)
This quasi-experimental study is designed to compare the effectiveness of cooperative learning with the traditional teaching approach in teaching elementary Mandarin as a foreign language to non-native speakers in the University of Technology MARA Kedah branch campus. This study uses pre-test and post-test design. The sample consists of two BMD 151 Mandarin classes from the branch; one class acts as a control group and the other class as an experimental group. The total number of students taking part in this study is 51 ( 6 boys, 45 girls). The duration of this study is half semester (mid August - October 2004). During that duration, both groups were exposed to the same facilities, and used the same textbook and workbook. Though Quantitative technique is the main technique used in this study, qualitative techniques such as taped interviews, classroom observations and assessment questionnaires were utilized in this study as well.